Lost Islamic history reclaiming Muslim civilisation from the past - Alkhateeb, Firas (London Hurst & Co., 2014)
"Islam has been one of the most powerful religious, social, and political forces in history. Over the last 1400 years, from origins in Arabia, a succession of Muslim polities and later empires expanded to control territories and peoples that ultimately stretched from southern France, to East Africa to South East Asia. Yet many of the contributions of Muslim thinkers, scientists, and theologians, not to mention rulers, statesmen and soldiers, have been occluded. This book rescues from oblivion and neglect some of these personalities and institutions while offering the reader a new narrative of this lost Islamic history. The Umayyads, Abbasids, and Ottomans feature in the story, as do Muslim Spain, the savannah kingdoms of West Africa and the Mughal Empire, along with the later European colonisation of Muslim lands and the development of modern nation-states in the Muslim world. Throughout, the impact of Islamic belief on scientific advancement, social structures, and cultural development is given due prominence, and the text is complemented by portraits of key personalities, inventions and little-known historical nuggets. The history of Islam and of the world's Muslims brings together diverse peoples, geographies, and states, all interwoven into one narrative that begins with Muhammad and continues to this day."--P. [4] of cover.
Includes bibliographical references (p. 215-217)
Keywords: Islamic civilization; Islamic countries -- Civilization